Justiça Fiscal e (re)formulação da política tributária: uma leitura constitucional e hermeneuticamente comprometida: superando os óbices da (des)igualdade - Conselvan, Victor de Almeida (Universidade do Vale do Rio dos Sinos, 2022)
Social Social inequalities in Brazil, in a broad sense, are rooted in the colonial heritage, in the hegemony of economics and in the concept of Law linked to legal positivism. Fiscal policies are essential to reduce the levels of this degrading phenomenon from a Stat centered perspective. Therefore, this research aims to revolve the linguistic ground on which a tradition that misrepresents the political role of tax law according to the article 3 of the brazilian constitution (CF/1988). Thus, originally, the proposal is: on the grounds of Crítica Hermenêutica do Direito perspective – conceived as the basis theory –, to project the (re)formulation of the meaning of fiscal justice as a constitutional duty and legitimizing foundation of taxation. That is, it is argued that fiscal policies can no longer be dissociated from the constitutional project and must, inexorably, seek to reduce inequalities.
Keywords: Desigualdade; Tributação; Crítica hermenêutica do direito; Justiça fiscal; Positivismo jurídico; Inequality; Taxation; Hermeneutic critique of law; Tax justice; Legal positivism; ACCNPQ::Ciências Sociais Aplicadas::Direito